Extracellular vesicles derived from fibroblasts induced with or without high glucose exert opposite effects on wound healing and angiogenesis - Bian, Xiaowei; Li, Bingmin; Tang, Haowen; Li, Qiankun; Hu, Wenzhi; Wei, Qian; Ma, Kui; Yang, Yuguang; Li, Haihong; Fu, Xiaobing; Zhang, Cuiping (Frontiers in Surgery, 2022)
ABSTRACT Background: Communication between fibroblasts and endothelial cells is essential for skin wound repair and regeneration. Extracellular vesicles (EVs) are crucial for intracellular communication by transporting active molecules. However, whether EVs derived from diabetic fibroblasts can perform the nomal communication function is unclear. Here, we compared the effects of EVs from human skin fibroblasts (HSFs) induced with or without HG on the angiogenic function of endothelial cells and wound healing. Methods: We first collected EVs from HSFs cultured with normal glucose concentration (NG-EVs) or with HG concentration (HG-EVs) and applied them to treat human umbilical vein endothelial cells (HUVECs). The cells were divided into three groups: control group, NG-EVs group, and HG-EVs group. We then examined the proliferation, migration, apoptosis, and tube formation of HUVECs. To illustrate the mechanism, the expression of β-catenin, GSK-3β, and p-GSK-3β was detected by western-blot. Finally, NG-EVs or HG-EVs were used to treat the wounds of mice to determine their role in wound closure. Results: By DNA content detection, Annexin V/PI staining, and EdU staining, we found that NG-EVs promoted HUVEC proliferation, while HG-EVs exhibited an opposite effect (p < 0.05). Scratch assay and tube formation assay demonstrated that NG-EV promoted angiogenesis in vitro, while HG-EVs showed negative impact (p < 0.05). The expressions of β-catenin and p-GSK-3β in HUVECs were enhanced by NG-EVs and decreased by HG-EVs (p < 0.05). Additionally, the in vivo experiment demonstrated that NG-EVs effectively promoted wound healing by locally enhancing blood supply and angiogenesis. In contrast, HG-EVs leaded to delayed wound closure and reduced blood supply and angiogenesis (p < 0.05). Conclusion: NG-EVs and HG-EVs exert opposite effects on wound healing and angiogenesis possibly by regulating GSK-3β/β-catenin signaling pathway. This research may provide a new treatment strategy for wound healing and illustrate the mechanism for impaired angiogenesis in diabetics.